Education for the Gifted and Talented: Student teachers reflecting about autonomy, control, and pedagogical diagnostics in a self-designed workshop program for gifted schoolchildren - David Rott (Hanze UAS, 2019)
In German schools, gifted education becomes more and more relevant, but it is still rare in universities. University students in teacher education especially have only few opportunities to develop their talents in special programs like honors programs. This paper presents the results of a project in which student teachers designed three workshops on the basis of their own interests and strengths and planned these with school teachers. To begin with, an overview over the honors programs in Germany is presented. The control and development of pedagogical diagnostics are discussed by a focus group from the perspective of the trainee teachers who developed the workshops for gifted gymnasium (i.e. grammar school) students, including their reflection of the degree of autonomy they experienced. The evaluation data were analyzed by the method of qualitative text analysis (Kuckartz, 2016) with a focus on the categories 'autonomy and control' and 'pedagogical diagnostics.' The central topic is the experience of competence in these fields.